2015
DOI: 10.3109/13697137.2015.1107039
|View full text |Cite|
|
Sign up to set email alerts
|

Vulvar and vaginal atrophy in four European countries: evidence from the European REVIVE Survey

Abstract: Objectives The aim of the European REVIVE survey was to achieve a better understanding of vulvovaginal atrophy (VVA), a chronic and progressive condition after menopause. We investigated perceptions, experiences and needs in terms of sexual and vaginal health in a sample of European postmenopausal women. Methods An online internet based survey was conducted in Italy, Germany, Spain and the UK with a total surveyed sample of 3768 postmenopausal women (age: 45–75 years). Results The most common VVA symptom was v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
165
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(179 citation statements)
references
References 29 publications
4
165
1
9
Order By: Relevance
“…[11][12][13][14] In our study, 51.9 % of women were sexually active which were comparable to the study of 58.6%, 51%, 52% and 40% sexually active in shah et al 15 , Nappi RE et al 16 , Jennifer S et al 17 and Versi E et al 18 studies respectively.…”
Section: Discussionsupporting
confidence: 85%
“…[11][12][13][14] In our study, 51.9 % of women were sexually active which were comparable to the study of 58.6%, 51%, 52% and 40% sexually active in shah et al 15 , Nappi RE et al 16 , Jennifer S et al 17 and Versi E et al 18 studies respectively.…”
Section: Discussionsupporting
confidence: 85%
“…Conducted in 2014, the European REVIVE survey [2] used the same methodology as the original US REVIVE survey [5]. Briefly, women aged 45-75 years and living in Italy, Germany, Spain, or the UK were screened for eligibility based on cessation of menstruation, menopause, and lifetime history of VVA symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…The European REVIVE study [2] and other international studies [8,9,13,14] reveal cultural differences in the impact of VVA on female sexuality and relationships. A recent European interview-and survey-based study further identified personality traits as an important factor influencing women's attitudes and behavior regarding VVA [15].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations